Pengaruh Keberadaan Kampus Universitas Islam An Nur Lampung Terhadap Kondisi Ekonomi Masyarakat Desa Sidoharjo Dalam Prespektif Ekonomi Syariah - Alvina Alvina; Lisa Efrina; Zulfa Rohmawati (Sharing: Journal of Islamic Economics Management and Business, 2024)
The point of this examination is to decide the impact of the presence of A Nur Lampung Islamic College on the monetary states of the encompassing local area. The Impact of the Presence of A Nur Lampung Islamic College on the Financial States of the Sidoharjo Town People group in a Sharia Monetary Viewpoint (Contextual investigation of the Sidoharjo Town People group, Jatiagung Locale, South Lampung Rule). The strategy utilized in this exploration is a quantitative examination technique. The number of inhabitants in this study were occupants of Sidoharjo Town who had the situation with Head of Family. Corresponding arbitrary examining method. The example in this study was 25 heads of families spread across two villas in Sidoharjo Town. The information utilized is information on the quantity of family heads (KK) in every villa. The assortment strategy is as documentation and surveys. The information was handled and dissected utilizing the cross organization information examination strategy (crosstab). The exploration results show that the presence of the A Nur Lampung Islamic College grounds for the most part emphatically affects new financial development. In light of the presence of the A Nur Lampung Islamic College people group, financial circumstances should be visible from the synchronous cost assurance coefficient r table. The consequences of the examination acquired a rtable cost of 0.511. In this manner, it shows that the presence of A Nur Lampung Islamic College impacts financial circumstancesWatchwords: Islamic Economics¸ Social Circumstances, College